IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS POKOK BAHASAN GLOBALISASI KELAS VI SD NEGERI 047175 DESA SIMACEM BEKERAH TAHUN PELAJARAN 2017/2018 - Pelista Br Karo Sekali (Universitas Quality, 2019)
Learning models that are in accordance with the needs of the subject matter will create a quality learning process, so that predetermined competencies are achieved. To be able to apply a learning model that is in accordance with IPS subject matter, an effective teacher has the ability to use a variety of learning models. Problem solving learning model is a learner-centered learning model by confronting these students with various life problems, the purpose of which is to stimulate the development of creative and comprehensive thinking skills of students in solving problems. The implementation of learning uses a Problem Solving Learning Model with good credibility, and student learning outcomes are completed and increased in the eyes of Social Studies Subjects Main Discussion on Globalization Class VI Public Elementary School 047175 in Simacem Village Spreads Academic Year 2017/2018